Pengaruh Model Pembelajaran Berbasis Proyek (PjBL), Model Pembelajaran Berbasis Multikultural (PBM) terhadap Altruisme Siswa SDN Margerejo I Surabaya. - Prastyo, Danang; Sulistyowati, Ida; Satianingsih, Rarasaning; Prameswari, Dinda (Jurnal Simki Pedagogia, 2024)
This research aims to determine the effect of learning models, namely the Project Based Learning Model (PjBL) and the Multicultural Based Learning Model (PBM) on the altruism of students at Margerejo I Elementary School, Surabaya. This type of research uses experiments with two classes, namely the treatment class and the control class. The research design uses a Posttest Only Non Equivalent Group Design. The research population is elementary school students in Surabaya and the research sample is SDN Margerejo I Surabaya. Data collection techniques using Altruism questionnaires. The data analysis technique uses the T test with the SPSS program. From the results of data processing, it was concluded that there was an influence of the PjBL and PBM models on the altruism of students at SDN Margerejo I Surabaya.